An Antipodean History of Interpretation1. Issue 3 (September 2014) - Boswell, John; Corbett, Jack
<x xml:space="preserve">Abstract</x> In this paper, we explore the connections between intepretivism's core and its peripheries in both geographical and epistemological terms, by tracing the relationship between interpretivism and Australian political scholarship. In this task, we draw on some of the most celebrated and influential work on Australian politics—by political scientists but before them historians and anthropologists—to show how the approach typically undertaken by these researchers echoes key tenets of interpretivism, especially through an interest in subjective beliefs and experiences, a desire to uncover and bring to life richly contextualised detail, and a commitment to the abductive linking of theory and practice. As such, we suggest that the spread of this counter identity to interpretive researchers in Australia risks manufacturing a sense of methodological antipathy, marginalising the work of interpretivists from mainstream political scholarship.